Can pancreatic duct stenting prevent post-ERCP pancreatitis in patients who undergo pancreatic duct guidewire placement for achieving selective biliary cannulation? A prospective randomized controlled trial - Ito, Kei; Fujita, Naotaka; Noda, Yutaka; Kobayashi, Go; Obana, Takashi; Horaguchi, Jun; Takasawa, Osamu; Koshita, Shinsuke; Kanno, Yoshihide; Ogawa, Takahisa (Journal of gastroenterology, 2010)
Background Although pancreatic duct guidewire placement (P-GW) for achieving selective biliary cannulation is reported to be effective in patients in whom endoscopic retrograde cholangiopancreatography (ERCP) is difficult, this technique entails a possible increased risk of post-ERCP pancreatitis. We conducted a prospective randomized controlled trial to evaluate the prophylactic effect of pancreatic duct stenting on the frequency of post-ERCP pancreatitis in patients who underwent P-GW. Methods Seventy patients who underwent P-GW for achieving selective biliary cannulation were included in this study. Patients were randomly assigned to either the stent group (n = 35) or the no-stent group (n = 35). The pancreatic duct stent used was a 5-Fr, 4-cm-long stent with a single pigtail at the duodenal end (Pit-stent™). The primary endpoint was the frequency of post-ERCP pancreatitis. Results Selective biliary cannulation was achieved in 80% of the stent group and in 94% of the no-stent group (P = 0.15). Post-ERCP pancreatitis occurred in 13% (9 patients; mild). Pancreatic duct stenting was successful in 91% of the stent group. One patient in the stent group developed migration of the stent during the procedure, followed by mild pancreatitis. The frequency of post-ERCP pancreatitis in the stent group was significantly lower than that in the no-stent group (2.9 vs. 23%, relative risk 0.13, confidence interval 0.016, 0.95). Conclusion Pancreatic duct stenting after P-GW for achieving selective biliary cannulation is recommended to reduce the incidence of post-ERCP pancreatitis.